Age-Related Differences in Motivations and Barriers to Physical Activity: A Cross- Sectional Analysis Across the Lifespan - Chruścińska, Agnieszka; Smoleńska, Olga; Muszkieta, Radosław; Hagner-Derengowska, Magdalena; Michalska, Anna (Journal of Education, Health and Sport, 2026)
Physical activity is a key element of a healthy lifestyle and the quality of human functioning at every stage of life. Despite the widespread availability of knowledge about its health-promoting effects, the level of physical activity in the population remains insufficient. The aim of this article is to analyze the motives for engaging in physical activity and the barriers that hinder its regular participation in various age groups, as well as to assess the relationship between activity levels and selected socio-demographic factors. The study was quantitative in nature and was conducted using a diagnostic survey method using a proprietary online questionnaire. Data analysis was conducted using descriptive statistics and nonparametric statistical tests. The obtained results indicate significant differences in the structure of motives for engaging in physical activity between age groups. In younger groups, aesthetic and social motives dominated, while in older groups, health and functional motives dominated. The most frequently reported barriers were lack of time, work-related fatigue, and health problems. The study's conclusions emphasize the need to differentiate physical activity promotion activities depending on age and life situation.